Cell membrane integrity of candida albicans after different protocols of microwave irradiation - Campanha, Nara Hellen; Jorge, Janaina Habib [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Oliveira, Caio Sergio Botta Martins de; Nordidovigo, LÍvia [UNESP]; Maia, Danielle Cardoso G. [UNESP]; Pavarina, Ana Cláudia [UNESP] (Science and Education Publishing, 2013)
To evaluate the ability of low time microwaveexposureto inactivate and damage cell membrane integrity of C. albicans. Materials and Methods: Two 200ml C. albicans suspensions were obtained. Sterile dentures were placed in a beaker containing Experimental (ES) or Control suspensions (CS). ES was microwaved at 650 W for 1, 2, 3, 4 or 5 min. Suspensions were optically counted using Methylene blue dye as indicative of membrane-damaged cells; spread on Agar Sabouraud dextrose (ASD) for viability assay; or spectrophotometrically measured at 550nm. Cell-free solutions were submitted to content analyses of protein (Bradford and Pyrogallol red methods); Ca++ (Cresolphthalein Complexone method); DNA (spectrophotometer measurements at 260nm) and K+ (selective electrode technique). Data were analyzed by Student-t test and linear regression (α=0.05). In addition, flowcytometry analysis of Candida cells in suspensionwas performed using propidium iodide. Results: All ES cells demonstrated cell membrane damage at 3, 4 and 5 min,viable cells were nonexistent at 3, 4 and 5 min ES ASD plates and optical density of ES and CS was not significantly differentfor all exposition times. ES cells released highcontents of protein, K+ , Ca++ and DNA after 2 min exposition when compared to that of the CSs. Similar results were observed with flow cytometry analysiswith regard to the periodsof microwave exposure. Conclusions: Microwave irradiation inactivated C. albicansafter 3min and damaged cell membrane integrity after 2 min exposition.
Keywords: Microwaves; Candida albicans; Denture stomatitis; Disinfection; Denture